2000
DOI: 10.4039/ent132591-5
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE TO SITODIPLOSIS MOSELLANA (DIPTERA: CECIDOMYIIDAE) IN SPRING WHEAT (GRAMINEAE)

Abstract: Cultivars of winter wheat, Triticum aestivum L., previously identified as possible sources of resistance to wheat midge, Sitodiplosis mosellana (Géhin), were crossed with spring wheat to produce lines with a spring growth habit and assure synchrony between insect and plant. Many of the lines showed low levels of infestation by wheat midge in the field, and 21 of these were tested for resistance in the laboratory. All test lines exhibited resistance, ranging from 58 to 100% suppression of larvae and 70 to 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(100 citation statements)
references
References 13 publications
6
94
0
Order By: Relevance
“…On the other hand, Skalmeje cultivar has also this wm1 marker, and it is a resistant cultivar, therefore, midge's infestation was very low as confirmed by Schliephake (2009, personal communication). the low densities of wheat midge on resistant wheat in this study are consistent with those found in previous studies conducted with different objectives (Lamb et al 2000a;Smith et al 2004). Similar results were obtained by (Smith et al 2007), pointing that wheat midge developing on resistant wheat was always very low compared with that of larvae developing on susceptible wheat cultivars and also they mentioned that small numbers of S. mosellana matured larvae in each wheat cultivar carrying the Sm1 gene for antibiosis resistance against this insect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, Skalmeje cultivar has also this wm1 marker, and it is a resistant cultivar, therefore, midge's infestation was very low as confirmed by Schliephake (2009, personal communication). the low densities of wheat midge on resistant wheat in this study are consistent with those found in previous studies conducted with different objectives (Lamb et al 2000a;Smith et al 2004). Similar results were obtained by (Smith et al 2007), pointing that wheat midge developing on resistant wheat was always very low compared with that of larvae developing on susceptible wheat cultivars and also they mentioned that small numbers of S. mosellana matured larvae in each wheat cultivar carrying the Sm1 gene for antibiosis resistance against this insect.…”
Section: Discussionsupporting
confidence: 92%
“…resistance to the wheat midge is partially dominant due to expression of the Sm1 resistance as single gene , that mediates an induced hypersensitive response in the surface of developing seeds where wheat midge larvae begin feeding, resulting in larval death (Ding et al 2000;lamb et al 2000a). in the wheat midge, the resistance act as an antibiotic reaction that includes elevation of phenol compound levels and results in the death of the young larvae shortly after they begin feeding (Ding et al 2000;Harris et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments were conducted on three wheats: the cultivar ÔRoblinÕ that is highly preferred for oviposition and suitable for larval development (Lamb et al 2000a); the cultivar ÔSuperbÕ that is less preferred for oviposition in the laboratory than ÔRob-linÕ but susceptible to infestation in the Þeld ; and the breeding line ÔKey 97Ð10Õwhich is not preferred for oviposition either in the laboratory and the Þeld, and is antibiotic for larval development (Lamb et al 2000a. The previously published ovipositional preferences were identiÞed in multi-line screening trials that did not consider plant developmental stages.…”
Section: Methodsmentioning
confidence: 99%
“…Wheat midge females prefer to oviposit at particular plant growth stages (Ding and Lamb 1999), and on some wheat genotypes (Lamb et al 2000a. Wheat defends itself against larval feeding in at least two ways: 1) the feeding site is suitable for larvae only at an early stage of seed development (Ding and Lamb 1999); 2) some wheat genotypes exhibit a hypersensitive reaction that kills feeding larvae, even on seeds at a stage that is normally suitable for their development (Lamb et al 2000a). Both defenses are associated with increased production of phenolic acids by the plant, acting in a dose dependent way on the survival of feeding larvae.…”
mentioning
confidence: 98%
See 1 more Smart Citation